Effect of spark timing on the performance of a spark ignition engine running on biogas–hydrogen blends. Issue 6 (2nd November 2017) - Porpatham, E.; Ramesh, A.; Nagalingam, B.
ABSTRACT: The influence of hydrogen addition in small quantities to biogas was studied in a spark ignition (SI) stationary engine at different spark timings at fixed equivalence ratio of 0.92. At this condition the engine operated with good thermal efficiency in the neat biogas mode. A single-cylinder diesel engine modified to operate as a SI engine was employed. The speed was 1500 rpm and the throttle opening was fixed at 100% at a compression ratio of 13:1. The maximum power output and thermal efficiency were achieved at a hydrogen energy share of 10%. Beyond this the engine experienced rough operation due to rapid combustion. However, nitric oxide (NO) emissions were high at this condition. At 5% hydrogen addition the hydrocarbon (HC) emission was significantly reduced with good thermal efficiency. NO levels were also low with 5% hydrogen addition as compared to neat biogas operation as retarded ignition timings could be used. The optimum ignition timings were significantly retarded, as the hydrogen quantity was raised. The best operating condition was 5% hydrogen share with a spark timing of 20°bTDC (before Top Dead Centre). It is concluded that addition of small amounts of hydrogen to biogas can significantly improve biogas engine operation.